Big-up yourself! The Return to Self-Promotion - Astghik Mavisakalyan; Michael Palmer; Silvia Salazar (Global Labor Organization (GLO), 2025)
Self-promotion plays a significant role in both the labor market and society; however, its prevalence and effects remain difficult to quantify. This paper leverages the unique setting of professional surfing to examine the causal impact of self-promotion-proxied by the act of "claiming" a wave-on performance outcomes. Utilizing data from over 5,500 waves in the World Surf League and employing an instrumental variables approach, we find that self-promotion provides substantial benefits, increasing wave scores by approximately 0.8 standard deviations, or 1.6 points out of a maximum score of 10. Notably, female surfers are significantly less likely than their male counterparts to engage in self-promotional behaviors, as reflected by a lower ferquency of claiming, yet they receive comparable benefits when they do claim. These findings offer valuable insights into the rewards of self-promotion in competitive, high-stakes environments and underscore the potential for women to improve outcomes by more frequently adopting such behaviors.
Keywords: J24; J16; Z22; 330; Self-promotion; Performance evaluation; Professional surfing; Gender differences; Instrumental variables